(untitled) (Journal of Laboratory Animal Science, 2025)
Moringa oleifera Lam. leaves (MOL) have been a staple food source in India for centuries. Recent reports have highlighted their potential as immunomodulators, hepatoprotectants, and more. To verify these claims and provide a robust solution for protein energy malnutrition, we conducted a study aimed at shedding light on the nutritional benefits of MOL consumption. This six-week study employed an isocaloric and isonitrogenous feeding trial, using a pelleted diet with 20% protein, supplemented with either 2% or 4% MOL. Healthy adult male rats were subjected to a unique forced exercise regimen. We analyzed the biochemical parameters of 30 rats distributed across five groups. It showed that the test groups had significantly lower levels of serum urea and liver enzymes (AST, ALT, and ALP) compared to the control group. Total protein levels increased significantly (14-19%) in all test groups, with no significant difference in creatinine levels. This analysis concludes that administering MOL powder orally at doses of 2% and 4% is biochemically safe and exhibits liver-protective and nephroprotective properties. Our study suggests that MOL powder can be safely incorporated into both human and animal diets in a dose-dependent manner. Additionally, the synergistic effect of exercise enhances these benefits. Notably, our unique model provides long-term results without altering animal behavior, making MOL a promising option for combating protein-energy malnutrition and malnutrition in India.